MECHANISM OF CONSTITUTIONAL REVIEW IN THE CONSTITUTIONAL COURT: A COMPARATIVE STUDY BETWEEN INDONESIA AND ROMANIA - Muhammad Nur Aiman (Universitas Negeri Semarang, 2026)
Constitutionality review is an important instrument in modern constitutional states to ensure the supremacy of the constitution. This article discusses the comparison of constitutional review mechanisms for laws in the Constitutional Court between Indonesia and Romania. Both countries share similarities in the civil law legal system, the unitary state form, and the republican form of government, and both place the authority for constitutional review in the Constitutional Court. This research employs normative legal research methods with a comparative approach, based on the rule of law theory and comparative law theory. The results show that Indonesia applies an a posteriori mechanism (after the law is enacted) with broad petitioner access, including individual citizens. In contrast, Romania applies a dual mechanism: constitutional preview (a priori) for draft laws and ratification of international treaties, and constitutional review (a posteriori) for laws through judicial channels and Parliamentary Regulations. Romania imposes stricter limitations on petitioners. Another difference lies in the legal consequences of decisions, where the decisions of the Indonesian Constitutional Court are final and binding from the moment they are pronounced, whereas in Romania, provisions declared unconstitutional lose legal force after 45 days if not remedied by the legislature. This comparison shows that despite similarities in legal systems, political dynamics and institutional design greatly influence the constitutional review mechanisms in each country.